DEVELOPING OF A WEBSITE-BASED INFORMATION SYSTEM FOR DASA WISMA TO REALIZE THE HEALTHY INDONESIA PROGRAM WITH FAMILY APPROACH (PIS-PK) - Muhammad Fahri Tarigan; Salsa Nabilla Afrimadani; Bintang Kurniawan; Sofia Naning Hertiana; Bagus Aditya (STKIP PGRI Tulungagung, 2025)
Dasa Wisma is a group of mothers consisting of 10 to 20 households in an urban village that holds important positions in the Family Welfare Empowerment (PKK) program to assist the community in considering family health. The Indonesian government has implemented various programs to provide healthcare for Indonesian people, one of which is the Healthy Indonesia Program with a Family Approach (PIS-PK). In Rancabolang Urban Village, the management of citizen data is still manual, which can hinder the performance of dasa wisma, making it ineffective and inefficient. This research aims to develop a website-based information system to assist dasa wisma in managing data, collecting recapitulated data, and exchanging information. The specifications of the information system are determined based on the Ministerial Regulation of the Republic of Indonesia No. 39 Year 2016 and interviews. The system is tested using the Black Box Testing method to ensure that the website works successfully. The User Acceptance Test conducted with users obtained a result of 90% (very good), demonstrating that the website functions according to user requirements. Testing using Wireshark to capture the average network traffic delay with the ITU-T G.1010 Quality of Service (QoS) standardization showed that the SIDALA website received a result of 1.06 seconds/page, which complied with the standard. The development of a website-based family health information system can increase the efficiency and effectiveness of health services, as well as facilitate reporting to related parties.